Implementasi Problem Based Learning dalam Meningkatkan Motivasi Belajar Siswa - Helpita, Leli (Center for Religious Studies and Social Empowerment Foundation, 2023)
This research aims to see and analyze the implementation of the problem based learning model in increasing student learning motivation at Al Falah Pasir Putih Bungo Private Madrasah Aliyah. The main problem raised is why is the learning process for the subject of moral beliefs not going well, which is indicated by problems with students' learning motivation? The research findings show that the implementation of the problem based learning model at Al Falah Pasir Putih Bungo Private Madrasah Aliyah must be improved further, because the practice of the problem based learning model has not been realized effectively in the classroom learning process. Student learning motivation at Al Falah Pasir Putih Bungo Private Madrasah Aliyah is experiencing a phase of decline. Meanwhile, the obstacles faced include; student management and differences in student character and self-control. The efforts made include; recording the systematic course of learning and applying it, elaborating on problem-based learning models with good learning methods, as well as appreciating achievements and giving punishments. Penelitian ini bertujuan untuk melihat dan menganalisis implementasi model pembelajaran problem based learning dalam meningkatkan motivasi belajar siswa di Madrasah Aliyah Swasta Al Falah Pasir Putih Bungo. Permasalahan utama yang diangkat adalah mengapa proses pembelajaran mata pelajaran akidah akhlak belum berjalan dengan baik yang ditandai dengan adanya permasalahan motivasi belajar siswa? Temuan penelitian menunjukkan bahwa implementasi model pembelajaran problem based learning di Madrasah Aliyah Swasta Al Falah Pasir Putih Bungo harus ditingkatkan lagi, karena praktik model pembelajaran problem based learning belum terealisasi secara efektif dalam proses pembelajaran di kelas. Motivasi belajar siswa di Madrasah Aliyah Swasta Al Falah Pasir Putih Bungo mengalami fase penurunan. Sedangkan kendala yang dihadapi antara lain; pengelolaan siswa dan perbedaan karakter siswa dan pengendalian diri. Adapun upaya yang dilakukan antara lain; mencatat sistematika jalannya pembelajaran dan menerapkannya, mengelaborasikan model pembelajaran problem based learning dengan metode pembelajaran dengan baik, serta mengapresiasi prestasi dan memberi hukuman.